Aeroelastic analysis and characterization of three-degree-of-freedom systems with discontinuous nonlinearity - Vasconcellos, R. [UNESP]; Bouma, A.; Marques, F.; Abdelkefi, A.; Hajj, M. R.; AIAA (Amer Inst Aeronautics & Astronautics, 2020)
The effects of freeplay, multi-segmented, and impact nonlinearities in the pitch and control surface degree of freedoms on the behavior of a three-degree of freedom aeroelastic system are investigated. The aeroelastic system consists of a plunging and pitching rigid airfoil supported by a linear spring in the plunge degree of freedom, a nonlinear torsional spring in the pitch degree of freedom and a control surface with a nonlinear spring in the trailing edge. The unsteady representation based on the Duhamel formulation is used to model the aerodynamic loads. Using modern methods of nonlinear dynamics, a nonlinear characterization is performed to identify the system's response. Observations of this study show that grazing/sliding behavior are present as well as nonlinear coupling between the frequencies of the system, leading to a complex behavior, sudden transitions between harmonic and chaotic responses as freestream velocity is increased. These discontinuous characteristics can lead to the occurrence of sudden amplitude variations and broadband oscillatory behavior that can result in catastrophic structural failures in aeroelastic systems.